A joint effort: The interplay between the innate and the adaptive immune system in Lyme arthritis - Brouwer, Michelle A. E. (Immunol Rev, 2020)
Articular joints are a major target of Borrelia burgdorferi, the causative agent of Lyme arthritis. Despite antibiotic treatment, recurrent or persistent Lyme arthritis is observed in a significant number of patients. The host immune response plays a crucial role in this chronic arthritic joint complication of Borrelia infections. During the early stages of B. burgdorferi infection, a major hinder in generating a proper host immune response is the lack of induction of a strong adaptive immune response. This may lead to a delayed hyperinflammatory reaction later in the disease. Several mechanisms have been suggested that might be pivotal for the development of Lyme arthritis and will be highlighted in this review, from molecular mimicry of matrix metallopeptidases and glycosaminoglycans, to autoimmune responses to live bacteria, or remnants of Borrelia spirochetes in joints. Murine studies have suggested that the inflammatory responses are initiated by innate immune cells, but this does not exclude the involvement of the adaptive immune system in this dysregulated immune profile. Genetic predisposition, via human leukocyte antigen‐DR isotype and microRNA expression, has been associated with the development of antibiotic‐refractory Lyme arthritis. Yet the ultimate cause for (antibiotic‐refractory) Lyme arthritis remains unknown. Complex processes of different immune cells and signaling cascades are involved in the development of Lyme arthritis. When these various mechanisms are fully been unraveled, new treatment strategies can be developed to target (antibiotic‐refractory) Lyme arthritis more effectively.